2015
DOI: 10.3832/ifor1127-007
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchange characteristics of the hybrid Azadirachta indica × Melia azedarach

Abstract: The hybrid Azadirachta indica × Melia azedarach is a new plant variety obtained through somatic hybridization, showing high concentrations of active insecticidal substances in its seeds. The hybrid could grow normally in regions with an average annual temperature of 15 °C, therefore it will likely become a valuable new tree species in subtropical and warm temperate regions. However, the photosynthetic physiological characteristics of A. indica × M. azedarach remain unknown. The photosynthetic gas exchange of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In contrast, stomatal conductance was more sensitive to soil water deficit, displaying a proportionally greater reduction under stress compared to the rate of photosynthesis, as it was already detected by Valadares et al [30] for eucalyptus hybrids. Although a number of studies demonstrated synchronized decline of stomatal conductance and net photosynthesis [13,29,31,32], recent studies showed that net photosynthesis may not be necessarily affected by the reduction of stomatal conductance. Indeed, Hasanuzzaman et al [33] reported that stomatal conductance showed an earlier decline under mild to moderate stress than net photosynthesis, which abruptly dropped only at severe stress.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, stomatal conductance was more sensitive to soil water deficit, displaying a proportionally greater reduction under stress compared to the rate of photosynthesis, as it was already detected by Valadares et al [30] for eucalyptus hybrids. Although a number of studies demonstrated synchronized decline of stomatal conductance and net photosynthesis [13,29,31,32], recent studies showed that net photosynthesis may not be necessarily affected by the reduction of stomatal conductance. Indeed, Hasanuzzaman et al [33] reported that stomatal conductance showed an earlier decline under mild to moderate stress than net photosynthesis, which abruptly dropped only at severe stress.…”
Section: Discussionmentioning
confidence: 99%
“…The observed decrease in the photosynthetic rate during the flowering stage in this study might be due to a reduction in stomatal conductivity and was also explained by [23] in olive trees. Photosynthetic rate and stomatal conductivity were found to decrease due to advancement in phenological stages were reported by [24], But in this study, these parameters showed an increasing trend with respect to different phenological stages of the trees.…”
Section: Among Rows Means With the Same Letters Indicates No Significant Difference Between Treatments At 5% Levels Of Lsdmentioning
confidence: 39%
“…According to [18], phenological phases were advanced, which led to a drop-in photosynthetic rate and stomatal conductivity [19].…”
Section: Stomatal Conductivitymentioning
confidence: 99%